2014
DOI: 10.1160/th14-05-0453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspirin intake at bedtime versus on awakening on circadian rhythm of platelet reactivity

Abstract: The risk of acute cardiovascular events is highest during morning hours, and platelet activity peaks during morning hours. The effect of timing of aspirin intake on circadian rhythm and morning peak of platelet reactivity is not known. It was our objective to evaluate the effect of timing of aspirin intake on circadian rhythm and morning peak of platelet reactivity. A randomised open-label cross-over trial in healthy subjects (n=14) was conducted. Participants used acetylsalicylic acid (80 mg) on awakening or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 49 publications
(57 reference statements)
2
19
0
Order By: Relevance
“…This study, however, was done in patients with essential thrombocytosis [21]. Furthermore, in line with previous research, we found a better early morning platelet inhibition in OD-evening in comparison with OD-morning [15,18,22]. Since cardiovascular events occur most frequently during late-night and early-morning hours [10], optimum platelet inhibition during these hours seems desirable.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study, however, was done in patients with essential thrombocytosis [21]. Furthermore, in line with previous research, we found a better early morning platelet inhibition in OD-evening in comparison with OD-morning [15,18,22]. Since cardiovascular events occur most frequently during late-night and early-morning hours [10], optimum platelet inhibition during these hours seems desirable.…”
Section: Discussionsupporting
confidence: 86%
“…Prior to storage at −80°C, the serum samples were centrifuged at 3000 x g for 10 minutes. STxB 2 was measured by enzyme immunoassay according to manufacturers' instructions (Thromboxane B2 Express, Cayman Chemicals, Ann Arbor, MI, USA) and previously described by Bonten et al [15]. Samples were analyzed in duplicate in the laboratory in order to measure the intra-assay coefficient of variance (CV), which was < 15% for all measurements.…”
Section: Serum Thromboxane B 2 (Stxb 2 )mentioning
confidence: 99%
“…For now, aspirin remains a cornerstone in secondary prevention of cardiovascular events [ 52 ]. Possible new treatment options include: i) a higher dose of aspirin [ 38 ]; ii) dosing of aspirin twice daily [ 29 , 40 ]; iii) intake of aspirin once daily at bedtime instead of in the morning [ 53 ] or iv) switching to or adding another antiplatelet agent such as the P2Y12-inhibitors clopidogrel, prasugrel or ticagrelor [ 54 ]. Finally, improving glycaemic control may also be a way of reducing platelet aggregation and outcome [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an exciting recent chronotherapy study, it was found that evening administration of low-dose aspirin reduces morning platelet reactivity, via COX-1 dependent pathways, as compared with taking aspirin upon awakening ( Bonten et al, 2014 ). This finding is consistent with earlier reports of a circadian rhythm in platelet surface markers ( Scheer et al, 2011 ), and in platelet aggregability ( Andrews et al, 1996 ).…”
Section: Chronotherapymentioning
confidence: 99%
“…Collectively these studies are clinically important because acute cardiovascular events (e.g., MI) are most likely to occur in the early morning hours vs. other times of day or night ( Muller et al, 1985 ), and platelet reactivity likely contributes to this early morning peak. Thus it is postulated that aspirin chronotherapy taken at bedtime instead of on awakening, as a preventative measure in healthy subjects and by patients with cardiovascular disease, can reduce the incidence of adverse cardiac events during the high-risk morning hours ( Bonten et al, 2014 ). That daily low-dose aspirin reduces the peak frequency of MIs in the morning and overall risk across the 24-h cycle ( Ridker et al, 1990 ), provides further support for this notion.…”
Section: Chronotherapymentioning
confidence: 99%